Dilemmas and challenges facing access to the Quilombola Brazil Program: The reality experienced by the Marques community (Emancipação, 2017)
This article aims to evaluate the access to the benefits offered by the Brasil Quilombola Program, within the Marques community in the municipality of Carlos Chagas, located in the Mucuri Valley in the State of Minas Gerais, Brazil. This community was certified in 2005 by the Palmares Cultural Foundation as "remnants of quilombos". For the accomplishment of the research that originated this article, it was used as technique the semi-structured individual interview, as well as the field observation. The analysis of the data allows to affirm that the access to the benefits offered by the Brasil Quilombola Program is extremely restricted, and that the lack of communication between the executor of the program and the possible users, as well as the execution failures, are the main ones responsible for the inefficiency and inaccessibility to the program.
Keywords: Brazil Quilombola Program. Community Marques. Remnant of Quilombo.